2007
DOI: 10.1093/jxb/erm191
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 canalizes developmental perturbation

Abstract: Stochastic processes are intrinsic phenomena that perturb developmental processes. However, the canalization process restricts the magnitude of perturbation and hence the magnitude of morphological variation during development. Heat-shock protein 90 (Hsp90) chaperones are a class of proteins stabilizing a network of 'client' proteins that are involved in diverse signal transduction pathways affecting development. Here it is reported that a reduction of Hsp90 gene dose creates canalization perturbations that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 35 publications
1
52
0
9
Order By: Relevance
“…Studies in the fruit fly and Arabidopsis strongly suggest that Hsp90 acts as a capacitor for morphological evolution by most likely neutralizing the conformational consequences of several mutations, therefore buffering their potential phenotypic changes and turning them phenotypically silent (Rutherford and Lindquist 1998;Queitsch et al 2002). Recent results in Arabidopsis have shown that Hsp90 restricts stochastic phenomena by minimizing perturbations, thereby canalizing development (Samakovli et al 2007). The Arabidopsis shd mutant phenotype could be the result of the accumulation of cryptic mutations, promoting morphological evolution in the Arabidopsis genome (Ishiguro et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the fruit fly and Arabidopsis strongly suggest that Hsp90 acts as a capacitor for morphological evolution by most likely neutralizing the conformational consequences of several mutations, therefore buffering their potential phenotypic changes and turning them phenotypically silent (Rutherford and Lindquist 1998;Queitsch et al 2002). Recent results in Arabidopsis have shown that Hsp90 restricts stochastic phenomena by minimizing perturbations, thereby canalizing development (Samakovli et al 2007). The Arabidopsis shd mutant phenotype could be the result of the accumulation of cryptic mutations, promoting morphological evolution in the Arabidopsis genome (Ishiguro et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One of such mechanisms is molecular chaperones -a group of proteins that respond to sudden increase in temperature or exposure to other environmental stresses (Feder & Hofmann, 1999;Salathia & Queitsch 2007;Sangster et al, 2004;Sørensen et al, 2003). Molecular chaperones, particularly Hsp90, also restrict stochastic phenomena within cells, by minimizing developmental perturbations, thereby canalizing the organism's development (Samakovli et al, 2007). Results presented in this study provide evidence that in Iris pumila plants the relative level of heat shock proteins Hsp70 and Hsp90 (Hsp90a and Hsp90b isoforms), varied significantly in a single generation, between the samples of local and foreign genotypes reciprocally transplanted to their original light habitats ("local vs. foreign" approach), and in the same genotype grown under alternative light conditions ("at home vs. away" approach), or among different seasons in the same habitat ("spring vs. summer").…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 has a strategic role in the developmental dynamics that govern early morphogenesis (Samakovli et al 2007). SHD, encoding an ER-resident HSP90-like protein, has a function in promoting elongation of pollen tube (Ishiguro et al 2002).…”
Section: Discussionmentioning
confidence: 99%